CONTROLLING AS A TOOL FOR ENHANCING THE EFFECTIVENESS OF STRATEGIC PLANNING IN PUBLIC ADMINISTRATION - Zalizniuk, Viktoriia; Kulchii, Inna; Zadorozhnyi, Volodymyr (Public Management and Policy, 2025)
The article examines controlling as a modern tool for enhancing the effectiveness of strategic planning in the field of public administration amid institutional transformations, decentralization, and increasing requirements for transparency and performance of public authorities. The relevance of the study is driven by the limited practice of systematic implementation of controlling in Ukraine’s public sector and the need to move from formal planning to data-driven management. The purpose of the article is to substantiate the role of controlling within the strategic management system of public authorities and to develop a model for its integration into the strategic planning process. The study employs methods of theoretical generalization, comparative analysis, a systems approach, structural-functional analysis, and logical modeling. A comparison of the classical business controlling concept with approaches to its adaptation in public administration is conducted, and the place of controlling as a coordinating and information-analytical function of strategic management is identified. The application of budgetary, financial, and operational controlling, strategic performance measurement systems (KPI, PI, strategic maps), and the process approach in the activities of public authorities is substantiated. The research findings indicate that the effective use of controlling is constrained by the insufficient development of analytical units, fragmentation of strategic planning, a lack of digital tools, and weak integration with strategy-oriented budgeting. Taking these issues into account, we propose a model for integrating controlling into the strategic planning system of public administration. Its application can support managerial decision-making, monitor the achievement of strategic goals, assess risks, and ensure timely response and adjustment of strategies. The practical significance of the results lies in the possibility of adapting the proposed model to different levels of public administration, which will contribute to greater coherence between strategic and budgetary decisions, enhanced analytical capacity of public authorities, and increased transparency and public trust in public institutions. Prospects for further research are associated with the development of digital controlling tools and the assessment of their impact on the quality of strategic management in the public sector.